Pengaruh Pemasaran Konten, Gaya Hidup Dan Ulasan Pelanggan Online Terhadap Keputusan Pembelian Pengguna Produk Suncreen Azarine Pada TikTok Dikota Malang Lowokwaru - Wulandarii, Dewi; Khalikussabir, Khalikussabir; Wahyuningtyas, Nanik (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research aims to determine the influence of Content Marketing, Lifestyle and Online Customer Reviews on purchasing decisions on TikTok Azarine sunscreen users in the city of Malang Lowokwaru. This research method uses quantitative research. The population in this study were consumers using Azarine sunscreen products in the city of Malang, Lowokwaru. Determining the sample size used the lameshow formula and obtained 96 respondents using a Likert scale. The data collection method uses questionnaires which are given online to respondents. The data analysis methods used in this research are instrument testing (validity test and reliability test), normality test, classical assumption test (multicolinearity test and heteroscedasticity test), multiple linear regression analysis, hypothesis testing (t test and coefficient of determination). using SPSS data processing. The results of this research partially show that the variables Content Marketing, Lifestyle And Online Customer Reviews have a significant influence on purchasing decisions. Keywords: Pemasaran Konten,, Gaya Hidup, Ulasan Pelanggan online dan keputusan pembelian